Female Labor Force Participation in Turkey : Trends, Determinants and Policy Framework - World Bank (Washington, DC, 2013)
Turkey has been collaborating with the World Bank in developing macroeconomic policies and implementing various reforms such as social security, investment climate, competitiveness, labor market, and public sector management. One of the salient features of the labor market in Turkey is the distinctly lower labor force participation (LFP) rates of women. As of January 2009, female LFP in Turkey was 23.5 percent. Urbanization and the move out of subsistence agriculture have had a profound effect on employment patterns for women, especially among those who have not attained university education. Family farming and subsistence agriculture have become less and less important as other more attractive opportunities expand in the service and manufacturing sectors. In the ninth development plan the Turkish Government has set goals to increase the number of women who are actively employed. The national action plan for gender equality emphasizes that using women's talents and skills in the labor market not only provides families with more economic independence, but also increases women's self-confidence and social respectability. Higher female employment is instrumental in building capacity for economic growth and poverty reduction. Higher levels of female employment allow government investments in education to be used more efficiently as women use their acquired talents. Policies that can help improve women's opportunities for more and better jobs in Turkey include: (a) creating job opportunities for first time job seekers; and (b) promoting early childhood development programs (ECD), such as preschool education and public or subsidized childcare programs.